Seminal traits, suitability for semen preservation and fertility in the native Portuguese horse breeds Puro Sangue Lusitano and Sorraia: Implications for stallion classification and assisted reproduction - Gamboa, Sandra (2008)
The Puro Sangue Lusitano (PSL) is the major national breed of horse in Portugal, but no studies exist on its seminal characteristics, or on the possibility of conserving semen for future use. The aim of this study was to evaluate semen parameters, fertility and the aptness to semen preservation in Lusitano Stallions. In order to compare characteristics defined by a single or by multiple semen collections per stallion 152 ejaculates obtained from 152 Lusitano stallions presented at an annual breeding soundness examination as well as data related to 371 ejaculates obtained from 9 PSL were analyzed. These latter samples were also evaluated in terms of their possible use in assisted reproduction and were compared with 113 ejaculates obtained from 4 Sorraia horses, a rare and endangered Portuguese breed. The percentage of motile spermatozoa (PMS) was assessed after collection (AC), after semen dilution (AD) and at 24 h of cool-storage. Mean values obtained for sperm motility and morphology and semen pH observed after semen collection differ significantly (P < 0.05) between single collection/multiple stallions and multiple collections/limited stallions, and no age related effects were detected. Overall, Lusitano semen quality was comparable to that of related breeds, while Sorraia stallions had very poor semen quality. The response to cool-storage of diluted semen samples differed among stallions and breeds, and the best results for progressive motile sperm cells at 24 h were in a range of 35-53% for PSL stallions and were lower for Sorraia stallions. Fertility rates obtained with artificial insemination (AI) averaged at 85% for PSL. With the exception of PMS AC, sperm vitality and semen pH no other seminal trait seemed to influence fertility rates in the Lusitano breed.